Prescribing Patterns of Amantadine During Pediatric Inpatient Rehabilitation After Traumatic Brain Injury: A Multicentered Retrospective Review From the Pediatric Brain Injury Consortium. Issue 4 (26th July 2022) - McLaughlin, Matthew J.; Caliendo, Eric; Lowder, Ryan; Watson, William D.; Kurowski, Brad; Baum, Katherine T.; Blackwell, Laura S.; Koterba, Christine H.; Hoskinson, Kristen R.; Tlustos, Sarah J.; Zimmerman, Kanecia O.; Shah, Sudhin A.; et al.
Abstract : Objectives: To describe dosing practices for amantadine hydrochloride and related adverse effects among children and young adults with traumatic brain injury (TBI) admitted to pediatric inpatient rehabilitation units. Setting: Eight pediatric acute inpatient rehabilitation units located throughout the United States comprising the Pediatric Brain Injury Consortium. Participants: Two-hundred thirty-four children and young adults aged 2 months to 21 years with TBI. Design: Retrospective data revie. Main Outcome Measures: Demographic variables associated with the use of amantadine, amantadine dose, and reported adverse effects. Results: Forty-nine patients (21%) aged 0.9 to 20 years received amantadine during inpatient rehabilitation. Forty-five percent of patients admitted to inpatient rehabilitation with a disorder of consciousness (DoC) were treated with amantadine, while 14% of children admitted with higher levels of functioning received amantadine. Children with DoC who were not treated with amantadine were younger than those with DoC who received amantadine (median 3.0 vs 11.6 years, P = .008). Recorded doses of amantadine ranged from 0.7 to 13.5 mg/kg/d; the highest total daily dose was 400 mg/d. Adverse effects were reported in 8 patients (16%); nausea/abdominal discomfort and agitation were most common, each reported in 3 patients. The highest reported dose without an adverse effect was 10.1 mg/kg/d. Conclusion: During pediatric inpatient rehabilitation, amantadine was prescribed to children across a range of ages and injury severity and was most commonly prescribed to older children with DoC. Dosing varied widely, with weight-based dosing for younger/smaller children at both lower and higher doses than what had been previously reported. Prospective studies are needed to characterize the safety and tolerability of higher amantadine doses and optimize amantadine dosing parameters for children with TBI.